Anti-programmed cell death-1 therapy in octogenarian and nonagenarian advanced/metastatic melanoma patients. Issue 1 (February 2021) - Cybulska-Stopa, Bożena; Ziętek, Marcin; Kamińska-Winciorek, Grażyna; Czarnecka, Anna M.; Piejko, Karolina; Galus, Łukasz; Ziółkowska, Barbara; Kieszko, Stanisław; Kempa-Kamińska, Natasza; Calik, Jacek; Zemełka, Tomasz; Kubiatowski, Tomasz; et al.
Abstract : Immunotherapy with anti-programmed cell death-1 (PD-1) agents is an effective treatment for metastatic melanoma. Octogenarians and nonagenarians represent a significant cohort of melanoma patients. This multicenter retrospective analysis enrolled 499 patients treated with nivolumab or pembrolizumab. Seventy-three patients were aged 80–100, 218 patients were aged 65–79, and 208 patients were <65 years old. Baseline parameters were comparable. The median overall survival (OS) was 14.7, 18.7, 25.9, and the median progression-free survival (PFS) was 8.7, 7.7, and 6.2 months in the age groups of 80–100, 65–79, and <65 years, respectively. The median melanoma-specific survival (MSS) was 22.5, 27.8, and 31.6 months in the age groups of 80–100, 65–79, and <65 years, respectively. There was no statistically significant difference in OS ( P = 0.2897), PFS ( P = 0.7155), and MSS ( P = 0.9235) between the group of 80–100 years old vs. 65–79 and vs. <65 years old patients. Overall response rate and disease control rate was similar in all groups ( P = 0.06974 and P = 0.89435, respectively). Overall, the immune-related adverse event (irAE) rate was comparable in the three age groups (41, 34, and 37.5% in the groups of patients aged 80–100, 65–79, and <65 years, respectively). Also, the rates of G3 and G4 irAEs were comparable (4, 6, and 7% in the groups of patients, respectively). The efficacy and toxicity of anti-PD-1 therapy in octogenarians and nonagenarians with metastatic melanoma are similar as in patients aged <65 years and 65–79 years. The patients' age should not be considered as an exclusion criterion for anti-PD-1 treatment. Abstract : Supplemental Digital Content is available in the text.